Perkin-Elmer employees with Scientific Data Systems unit - Perkin-Elmer Corporation (1966)
Group photograph of unidentified Perkin-Elmer Corporation employees gathered around a Scientific Data Systems (SDS) 9300 unit. Founded by Max Palevsky and Robert Beck in September 1961, Scientific Data Systems manufactured computers capable of large-scale scientific computations. Notably, the company was an early adopter of integrated circuits in computer design and the first to employ silicon transistors.
Keywords: Employees; Perkin-Elmer Corporation; Scientific apparatus and instruments; Computers; Corporations; Scientific Data Systems